Study of the bond behaviour between basalt fibre-reinforced polymer bar/sheet and bamboo engineering materials. Issue 14 (October 2019) - Lv, Qingfang; Ding, Yi; Liu, Ye
To improve practical application of modern bamboo structures, strengthening the bamboo engineering material is necessary to overcome insufficient stiffness. As an essential step in developing fibre-reinforced polymer–bamboo engineering material composite structures aimed at increasing the structural stiffness, the bonding behaviour at the interface of the fibre-reinforced polymer and bamboo engineering materials should be investigated in detail because currently there is a lack of research. In this article, bonding behaviour is studied between basalt fibre-reinforced polymer bar and bamboo engineering material including laminated and reconstituted bamboo and between basalt fibre-reinforced polymer sheets and laminated bamboo. Failure patterns are categorized, and the load–slip curves are discussed. Based on the failure pattern and strain variation, recommended bond lengths were proposed for the basalt fibre-reinforced polymer bar–bamboo engineering material and basalt fibre-reinforced polymer sheet–laminated bamboo composite specimens, respectively. In addition, a simplified three-phase bond–slip model was proposed for the basalt fibre-reinforced polymer bar–bamboo engineering material composite specimen.